Cultures of space and collective and participative artistic processes. recent cases in mexico city, bogota and medellin - Escobar Neira, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2012)
this article covers different aspects related to the spacialization of some cases of collective and participative artistic practices in specific places of three latin american cities: mexico city, bogota and medellin. therefore, the article questions the presence of different social ideologies and representations concerning the artistic field in its local and global dimensions, which establish meanings for the artistic, the political and social matters and, at the same time, fight among themselves when associating with certain contemporary artistic practices and its agents and institutions. in order to do so, it is proposed a focus that, to a certain extent, is separated from art theory and history, placing itself in a constant to and fro movement between the assumptions of artistic practices and social sciences.